PENGARUH TINGKAT KESULITAN KEUANGAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI - Setyaningsih, Hesty (Journal of Accounting and Investment, 2016)
This purpose of this research tests the influence of a company’s financial distress on its accounting conservatism. This research is experience influence the prediction difference between positive accounting theory and signaling theory about the influence of a company’s financial distress on its accounting conservatism. This research uses purposive sampling method and sample in this study consists of companies that were listed at Indonesian Stock Exchange since 2002 to 2006, companies manufacturing that experience net income negative since 2002 to 2006, accounting report period become extinct each 31 december, accounting report have data inside Indonesian monetary unit, so sample consists of 76 companies and have 173 observation data. Hypotheses are examined by using Ordinary Least Squares Regression. The results in this research tests indicate that a company’s financial condition positively influences its accounting conservatism and these support signaling theory prediction about the influence of a company’s financial distress on its accounting conservatism.